The Correlation between Multiple Intelligences and Students’ Achievement in Speaking Class at English Education Department, Universitas Muhammadiyah Yogyakarta - Dani Ratrianasari (PBI 15 UMY 040, 2015)
*40 Intelligence as one of the aspects in educational field becomes an urgent thing that must be considered in teaching and learning process. The purposes of this study were to find out the students’ most dominant intelligence, to know students’ speaking skill and to inspect the correlation between students’ most dominant intelligence and students’ speaking skill at EED UMY. This research used quantitative design with 59 students being participants of this study. The participants were students at English Education Department academic year 2014 that were in Listening and Speaking for Career Development classes. A set of questionnaire made by Branton Shearer which consisted of 30 items with four responses was distributed. The results revealed that students’ most dominant intelligence was the intrapersonal intelligence. From 59 participants, the intrapersonal intelligence gained the most significant result with 25 students were in the intrapersonal intelligence, five students were in linguistic intelligence, five people were in musical intelligence, four students were in logical-mathematical intelligence and one student was in visual-spatial intelligence. The results also indicated that there were seven other participants who had two dominant intelligences. For example they had intrapersonal and interpersonal intelligence which obtained the same score. The results showed there were four students who had three dominant intelligences. For instance a student had intrapersonal, logical-mathematical, and musical intelligence as the dominant intelligence. The results also showed one of the total participants had intrapersonal, interpersonal, linguistic, and visual-spatial intelligences as the dominant intelligence. The data vi on students’ speaking skill also showed that students of EED UMY 2014 had good ability in speaking skill because the value of mean was 16. Pearson Product Moment correlation (r) indicated that there was a weak correlation between students’ most dominant intelligence and students’ speaking skill (r = 0.03). Hence, the hypothesis of Ho was rejected and the hypothesis of H1 was accepted